The Turmoil of Tax Incentives for Micro-Enterprises on Innovation with Debt Investment as A Moderating Variable - Deranika Ratna Kristiana; Ika Puspita Kristianti (AIBPM Publisher, 2022)
This study aims to determine the reaction of micro business performers in utilizing tax incentives. It specifically analyzes tax incentive in the form of final income tax on income received by micro-businesses.Â Debt investments will strengthen and support micro-business in increasing venture capital. This study uses the explanatory method, tests the formulated hypotheses, and uses descriptive qualitative data by distributing questionnaires to respondents online who meet the criteria for micro-enterprises in the DI Yogyakarta region. Our findings indicate that not all micro-entrepreneurs take advantage of fiscal policies in the form of incentives for Final Income Tax borne by the government. Tax incentives do not significantly affect product or service innovation developed by micro-entrepreneurs. The moderation in debt investment triggers micro-entrepreneurs to invest in debt during this pandemic and use it to develop their products/services according to consumer needs.